Risk Factors for Acute Heart Failure in Patients with Infective Endocarditis - Koltunova, Hanna B. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. Acute heart failure (AHF) in patients with infective endocarditis (IE) is an independent indication for urgent cardiac surgery according to international guidelines. Preoperative risk factors for AHF in patients with IE empower to build the route of a patient rationally according to clinical status. The aim. To analyze clinically significant risk factors for AHF in patients with IE. Materials and methods. A retrospective single-center study was conducted which included clinical data of 311 patients with IE who were treated at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine for the period from January 1, 2019 to October 22, 2021. The mean age of the patients was 47.9 ± 3.83 (19 to 77) years. The proportion of men in the study was 81.7% (254 patients). The mean duration of IE was 2.6 ± 0.1 (1 to 11) months. Global database for IE patients was divided into separate cohorts with different problems associated with this pathology. Diagnosis of IE was established according to the Duke criteria. The causative agent was identified and results of antibioticogram were evaluated. All the patients were divided into classes according to the New York Heart Association (NYHA) functional scale. Patients with signs of AHF were assigned to NYHA class IV. There were 2 groups of patients: 252 (81.1%) patients without signs of AHF before surgery, 59 (18.9%) patients with preoperative AHF. The risk factors for the occurrence of AHF were analyzed. Statistical significance was set at p < 0.05. The intensive care unit length of stay and hospital length of stay were evaluated. Results. Risk factors for preoperative AHF in patients with IE: IE of the aortic valve (odds ratio (OR), 2.97 [1.57-6.91]) (p=0.003); concomitant inflammatory pathology of the lungs (OR 3.37 [1.55-7.11]) (р=0.003); linezolid resistance of the pathogen (OR 2.34 [1.07-4.26]) (р=0.026); vancomycin resistance of the pathogen (OR 2.25 [1.13-4.74]) (p=0.032); IE of the prosthetic heart valve (OR 1.155 [1.01-1.1]) (p=0.036); nosocomial nature of the disease (OR 2.14 [0.83-4.37]) (р=0.049). The intensive care unit length of stay was significantly longer in the group of patients with AHF (8.8 ± 0.7 days) than in the group of patients without AHF (4.8 ± 0.2 days) (р˂0.001). For 311 surgical interventions, the number of deaths was 7 (2.3%). The analysis of deaths according to the type of complications revealed that 4 (1.5%) patients died due to cardiac causes (263 cardiac complications). Among them, the largest share was made up of patients with AHF: 3 (1.4%). Conclusions. In clinical work, it is important to identify preoperative factors that are associated with the tactics of treatment of patients with IE in order to improve the results of cardiac surgery.